Live rubella vectors can express native HIV envelope glycoproteins targeted by broadly neutralizing antibodies and prime the immune response to an envelope protein boost. Issue 34 (16th August 2018) - Virnik, Konstantin; Nesti, Edmund; Dail, Cody; Scanlan, Aaron; Medvedev, Alexei; Vassell, Russell; McGuire, Andrew T.; Stamatatos, Leonidas; Berkower, Ira
Highlights: Live attenuated rubella vectors are based on the licensed rubella vaccine strain, which has shown safety, potency, and lifelong protection against rubella infection. It elicits systemic and mucosal immunity. As a vector, it can accommodate full length SIV Gag p27 and large domains of HIV gp120. We show: rubella vectors express Env with a native CD4 binding site that is the target of neutralizing antibodies. We combined a rubella vector prime and a recombinant protein boost to achieve a strong immune response. Abstract: Following HIV infection, most people make antibodies to gp120 and gp41, yet only a few make broadly neutralizing antibodies that target key antigenic sites on the envelope glycoproteins. The induction of broadly neutralizing antibodies by immunization remains a major challenge of HIV vaccine research. Difficulties include: variable protein sequence, epitopes that depend on the native conformation, glycosylation that conceals key antigenic determinants, and the assembly of Env trimers that mimic viral spikes. In addition, more potent immunogens may be needed to initiate the response of germline antibody precursors and drive B cell maturation toward antibodies with broad neutralizing activity. We have expressed HIV Env glycoproteins by incorporation into live attenuated rubella viral vectors. The rubella vaccine strain RA27/3 has demonstrated its safety and potency in millions of children. As a vector, it has elicited potent and durable immune responses in macaques to SIV Gag vaccine inserts. We now find that rubella/env vectors can stably express Env core derived glycoproteins ranging in size up to 363 amino acids from HIV clade C strain 426c. The expressed Env glycoproteins bind broadly neutralizing antibodies that target the native CD4 binding site. The vectors grew well in rhesus macaques, and they elicited a vaccine "take" in all animals, as measured by anti-rubella antibodies. By themselves, the vectors elicited modest antibody titers to the Env insert. But the combination of rubella/env prime followed by a homologous protein boost gave a strong response. Neutralizing antibodies appeared gradually after multiple vaccine doses. The vectors will be useful for testing new vaccine inserts and immunization strategies under optimized conditions of vector growth and protein expression.